Study of Charyn river naked osman (Diptychus dybowskii) nutrition and ichthyopathological analysis (International Journal of Biology and Chemistry, 2024)
The paper discusses the study of nutrition and ichthyopathological analysis of naked osman from the Charyn River, which is located on the territory of the Charyn State National Natural Park in the Almaty region. The naked osman belongs to the carp family. The fish does not have any scales on other part of the body exept the lateral line. The naked osman currently dwells in Kazakhstan, China, Kyrgyzstan, Uzbekistan, India, Nepal and other Asian countries. The purpose of the work is to determine the Charyn River’s food base and water condition by studying the food spectrum, fish pathology. To carry out the given study the fish were caught in the autumn in 2021. Only 15 samples of the caught fish were taken for the analysis. According to the ichthyological analysis results, the absolute length of 15 samples of the fish ranged from 8.3 cm to 12.7 cm, and their mass was from 4.81 g to 17.60 g. The standard quantitative - weight method was used for ichthyotrophological research. The special histological method was employed for ichthyopathological study. According to the ichthyotrophological study, the fullness index was about 10.75%00, and insect larvae were an essential food. Histological studies did not reveal an obvious pathology. As a result, the nutrient reserves in the reservoir were found to be at a good level and the external environment was found not to produce a negative effect on the fish.